Interplay of solar wind parameters and physical mechanisms producing the saturation of the cross polar cap potential - M. Myllys; E. K. J. Kipua; B. Lavraud (Geophysical Research Letters)
Abstract The nonlinear response of the cross polar cap potential (CPCP) to solar wind driving electric field is a well‐known phenomenon. The reasons behind this saturation, however, are still under debate. We have performed a statistical study of the coupling efficiency between the solar wind and the northern polar cap index (PCN). PCN is used as a proxy for the CPCP. Our main focus is in quantifying how the solar wind dynamic pressure alters the efficiency. We show that the saturation of PCN occurs both during low and moderate upstream MA conditions. We also show that the increasing dynamic pressure is associated with increasing PCN. In addition, we find that the coupling is different depending on which parameter, the velocity or the magnetic field, increases the solar wind driving electric field: the higher the velocity the higher the coupling efficiency.